Perlindungan Hukum Dalam Kasus Anak Korban Kekerasan Seksual Oleh Ayah Kandung Di Wilayah Hukum Kepolisian Resort Kupang Kota - Bengngu, Marrya Martha; Manuain, Orpa G; Leo, Rudepel Petrus (Law Faculty, Nusa Cendana University, 2024)
Children are a mandate from God whose human rights are regulated in the Constitution of the Republic of Indonesia Year 1945. This needs special attention from all circles, especially law enforcement. The formulation of this research problem is: (1). How are leegal proteection eforts for cases of child victims of sexual intercourse by biological father perpetators at the Kupang City Resort Police. (2). What are the obstacles faced by law enforcement officials in providing legal protection to child victims of sexual intercourse by biological father perpetrators at the Kupang City Resort Police. This research is an empirical legal research, with data collection techniques through interviews with 2 information respondents. The types of data used are primary and secondary data using collection techniques are interviews and literature studies that are processed and analyzed descriptively quantitatively. The results showed: (1). Legal protection efforts against cases of child victims of sexual intercourse by perpetrators of biological fathers at the Kupang City Resort Police are preventive protection efforts and repressive protection efforts. (2). The obstacles faced by law enforcement officials in providing legal protection to children with sexual intercourse by perpetrators of biological fathers in the Kupang City Resort Police are caused by infrastructure and community factors. The conclusion of this study is that legal protection efforts against cases of sexual intercourse by perpetrators of biological fathers in the Kupang City Resort Police have been running both Preventive and Repressive efforts, but there are still two obstacles to facilties and infrastructure and the community.